Perspectives of the Enterprise for the Americas Initiative - Torres, Víctor (1992)
The author tries to explain the sources and feasibility of the Enterprise for the Americas Initiative (or Bush proposal),  arising from the structural changes in the world system, which are characterized by a marked tendency towards a multipolar world. The author suggests that the US finds it necessary to establish a free trade zone with Latin America so as to enable the US economy to be on a better footing against the other two regional blocks led by the European Community and Japan.